ASUPAN MAKANAN , STATUS GIZI DAN LAMA HARI RAWAT INAP PADA PASIEN PENYAKIT DALAM DI RUMAH SAKIT ADVENT MANADO - Dhian Ayudhia Kasim; Vera T. Harikedua; Olga L. Paruntu (POLTEKKES KEMENKES MANADO, 2016)
Malnutrition can affect the function and healing every organ, such as changes in body weight,heart function and kidney decreases, system disorders digestive tract, bacterial or parasiticinfections and wounds difficult to heal as a result of the immune system is decreased,decreased capacity of re-feeding syndrome, and depression in patients , so important aconcern for hospitals weeks to make improvements nutritional status by fulfilling the energyneeds in an effort to support the patient's healing process. Research in Jakarta obtained dataon approximately 20-60% of patients have the status of malnutrition and the other 69%decreased nutritional status during inpatient hospital This study aimed to know therelationship between dietary intake, nutritional status and length of stay in Manado AdventistHospital.This research is descriptive analytic observational with cross sectional study conducted from13 April - May 13, 2016 in Manado Adventist Hospital with 43 samples. Criteria for adultpatients, has been undergoing treatment at least 2 days and get the hospital food.There are 74.4% of inpatients in Manado Adventist Hospital has a level of intake of ≤ 80%.Malnutrition status as much as 32.6% and the length of stay as much as 76.7% to thecategory of> 6 days. There is a relationship of food intake and nutritional status, andnutritional status and length of stay.